MEMBONGKAR KONSEP ETIKA BISNIS DALAM AL-QUR’AN: SEBUAH PERSPEKTIF EPISTEMOLOGIS - Syukron, Ahmad (IAIN Pekalongan, 2009)
In Islamic economics discipline, Islamic business ethic is a guidance to do business based on values that consist in Qur’an. The appearance of Islamic business ethic, as a matter of fact, plays very important role in changing assumption and understating of “amoral business system thought”, which glows in social life at present. By the appearance of Islamic business ethic, it is expected that business is no longer viewed as amoral activity that ignore ethical values.